KAJIAN GROUND SUPPORT EQUIPMENT (GSE) MOTORIZED PT GAPURA ANGKASA CABANG SOEKARNO HATTA - Mustika Sari; Oce Prasetya (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of this research is (1) to find out the use (utilization) of motorized equipment support at PT Gapura Angkasa branch office Soekarno Hatta Airport in 2015 equal to 214 appliances with request 244 appliances and (2) to find out the highest usage tools in 2015. Data presentation was using available equipment ground support data, equipment on demand, and tools that can not be used (idle). The explanation is supported by previous journals and thesis of ground support equipment as well as literature review of several theories related to it. The research results show that the use of GSE motorized ambulift equipment is 100% indicating that ambulift is used continuously and in reasonable condition to wear. The toolsused are the Ground Power Unit with 94% usage and followed by other devices with the same amount from 70% to 88% which means that the use of motorized ground support equipmentis is quite high.